2009
DOI: 10.1111/j.1752-1688.2009.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Denser Greener? An Evaluation of Higher Density Development as an Urban Stormwater‐Quality Best Management Practice1

Abstract: A simple spreadsheet model was used to evaluate potential water quality benefits of high-density development. The question was whether the reduced land consumed by higher density development (vs. standard suburban developments) would offset the worse water quality generated by a greater amount of impervious surface in the smaller area. Total runoff volume and per acre loadings of total phosphorous, total nitrogen, and total suspended solids increased with density as expected, but per capita loadings and runoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Before applying LID practices to urban developments, UHD land use might be the best choice for minimizing the impact of urbanization on surface runoff and pollutant loadings, as shown in other studies [17,18,35]. Jacob and Lopez [18] mentioned the advantage of higher density development outperforming traditional stormwater BMPs in pollutant reductions, due to the decrease of a runoff-generating area. However, after the application of LID practices to urban developments, all post-LIDs scenarios performed better than the UHD scenario (Table 5).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Before applying LID practices to urban developments, UHD land use might be the best choice for minimizing the impact of urbanization on surface runoff and pollutant loadings, as shown in other studies [17,18,35]. Jacob and Lopez [18] mentioned the advantage of higher density development outperforming traditional stormwater BMPs in pollutant reductions, due to the decrease of a runoff-generating area. However, after the application of LID practices to urban developments, all post-LIDs scenarios performed better than the UHD scenario (Table 5).…”
Section: Resultsmentioning
confidence: 93%
“…Seo [17] investigated how the amount of runoff and pollutant loadings were generated differently under three different urban planning designs and presented the compact high-density urban type as the most effective urban type. Jacob and Lopez [18] also evaluated the benefits of high density development for the reduction of water quality loadings in comparison with standard suburban developments, mentioning it as an effective approach more than traditional BMPs under their study conditions. Such studies imply that the effects of the application of LID practices could vary with different urban patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Well-planned urban areas potentially can support the lowest per capita quantities of chemical emissions possible for human settlements (e.g. Jacob and Lopez, 2009). Thus, urban areas can be managed to minimize environmental impacts, outside obvious point source regulations.…”
Section: Cities In the 21st Centurymentioning
confidence: 99%
“…They also reported that combined sewer overflow (CSO) and stormwater effluents contribute 4 to 23% to the indicator bacteria concentrations of the Tama River. A simple spreadsheet model was used to evaluate potential water quality benefits of high-density development in the United States [36]. They concluded that higher densities, such as those associated with transit-oriented development, could outperform almost all traditional BMPs, in terms of reduced loadings per a constant population.…”
Section: Sewer Water Qualitymentioning
confidence: 99%